Penguatan Partisipasi Sosial Dan Pemberdayaan Masyarakat Melalui Kuliah Kerja Nyata Tematik Di Kelurahan Pematang Gubernur - Pratiwi, Ii; Apriani, Ramalia; Nasution, Raihan Novanza; Saputra, Muhammad Azan Dwi; Ambarwati, Dea Ananda; Handayani, Lefi Evti; Khairil, Khairil; Yulianti, Liza (Jurnal Gotong Royong, 2026)
Social community participation is the basic capital in sustainable community development. This community service activity aims to strengthen social participation and empower communities through active involvement in mutual cooperation activities, morning exercises, routine religious gatherings, and joint celebrations. The implementation method uses a community-based approach with a participatory action strategy involving students as facilitators and the community as the main actors. Activities were carried out in RT 31 RW 02 Pematang Gubernur Village during December 2025 to January 2026 involving 5 students and more than 100 residents. The results show an increase in the frequency of citizen participation in social community activities, strengthening of social bonds between residents, and the formation of collective awareness about the importance of togetherness. This program successfully created a stronger atmosphere of togetherness and significantly improved the quality of community social life.